The "Big‐Bang" for modern glial biology: Translation and comments on Pío del Río‐Hortega 1919 series of papers on microglia. Issue 11 (November 2016) - Sierra, Amanda; de Castro, Fernando; del Río‐Hortega, Juan; Rafael Iglesias‐Rozas, José; Garrosa, Manuel; Kettenmann, Helmut
Abstract : The word "glia" was coined in the mid‐19th century and defined as "the nerve glue". For decades, it was assumed to be a uniform matrix, until cell theorists raised the "neuron doctrine" which stipulated that nervous tissue was composed of individual cells. The term "astrocytes" was introduced in the late 19th century as a synonym for glial cells, but it was Santiago Ramón y Cajal who defined a "third element" distinct from glial cells (astrocytes) and neurons. It was not until 1919 when Pío del Río‐Hortega, an alumnus of the Cajal School, introduced the modern terms we use today, and thoroughly described both "oligodendrocytes" and "microglia" to clearly distinguish them from astrocytes. In a series of four papers published that year in Spanish, Río‐Hortega described the distribution and morphological phenotype of microglia. He also noted that these cells were the origin of the rod cells described earlier in pathologic tissue, and recognized that resting microglia transformed into an ameboid phenotype in different types of brain diseases and pathologies. He also noted the mesodermal origin of these cells and recognized their phagocytic capacity. We here provide the first English translation of these landmark series of papers, which paved the way for modern glial research. To heighten the value and accessibility of these classic papers and their original figures, an introduction to this critical period of neuroscience is provided, along with unpublished photographs. By adding comments to the translated text, we provide sufficient context so that contemporary scientists may fully appreciate it. GLIA 2016;64:1801–1840 Main Points: An annotated English translation of the 1919 Pio del Río‐Hortega papers is provided. These papers contain the first modern definitions of the three types of CNS glial cells – microglia, astrocytes, and oligodendrocytes. Microglia are described in the normal and pathologic brain.